2001
DOI: 10.1093/humrep/16.6.1191
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of DNA integrity and morphology of ejaculated spermatozoa from fertile and infertile men before and after cryopreservation

Abstract: Cryopreservation of human spermatozoa is extensively used in artificial insemination and IVF programmes. Despite various advances in cryopreservation methodology, the recovery rate of functional post-thaw spermatozoa remains mediocre, with sperm motility being significantly decreased after freezing. This aim of this study was to investigate the effects of cryopreservation on both DNA integrity and morphology of spermatozoa from fertile and infertile men. Semen samples were obtained from 17 fertile and 40 infer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
143
1
10

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(163 citation statements)
references
References 53 publications
9
143
1
10
Order By: Relevance
“…The clinical significance of comet assay in correlating the DNA damage with sperm concentration, morphology, mitochondrial function and oocyte peneteration has been documented in previous studies [95][96][97]. In a study by O'Connell [98] it was reported that sperm isolated from semen by density centrifugation for ART have less DNA fragmentation.…”
Section: Clinical Aspects and Relevance Of Dna Integrity Testsmentioning
confidence: 93%
“…The clinical significance of comet assay in correlating the DNA damage with sperm concentration, morphology, mitochondrial function and oocyte peneteration has been documented in previous studies [95][96][97]. In a study by O'Connell [98] it was reported that sperm isolated from semen by density centrifugation for ART have less DNA fragmentation.…”
Section: Clinical Aspects and Relevance Of Dna Integrity Testsmentioning
confidence: 93%
“…Thus, cryostorage is wellknown to be associated with the induction of DNA damage and, again, a majority of this damage seems to be oxidative. 58,59 Similarly, heat exposure will induce free radical generation by the spermatozoa as a consequence of the initiation of apoptotic cascade, and so will exposure to radiofrequency electromagnetic radiation 21 or hydrogen peroxide. 52 All of these conditions are associated with the creation of oxidative stress.…”
Section: Triggers Of Apoptosismentioning
confidence: 99%
“…The freezing/thawing process has been shown to generate sperm DNA damage including DNA fragmentation, base modifications, chromatin cross-linking and other alterations, although the exact mechanisms of the cryoinjury to sperm DNA have not been fully elucidated. 4,15,71,72 Recent studies have shown that DNA fragmentation can be primarily attributed to cryopreservation-induced ROS. [73][74][75] In contrast to superoxide anion, the more stable H 2 O 2 readily crosses the plasma membrane and is responsible for DNA oxidative damage.…”
Section: Gangliosides and Spermatozoamentioning
confidence: 99%
“…[10][11][12][13][14] A beneficial effect of the in vitro supplementation of different natural or chemically synthesized antioxidant compounds on human spermatozoa has been observed; however, their effect has also been shown to decrease at inadequate concentrations and, even worse, to behave as pro-oxidants. 11,12,15,16 Herein, we discuss the protective role of exogenous gangliosides against ROS-induced changes based on our studies of human spermatozoa, leukocytes and cell-free systems. Of particular interest are differences between the effects of various types of gangliosides on the lipid peroxidation level, superoxide anion production [17][18][19][20] and H 2 O 2 and cryopreservation-induced DNA damage of human spermatozoa.…”
Section: Introductionmentioning
confidence: 99%